2004
DOI: 10.1007/s00253-004-1557-y
|View full text |Cite
|
Sign up to set email alerts
|

Reductive transformation of methyl parathion by the cyanobacterium Anabaena sp. strain PCC7120

Abstract: Organophosphorus compounds are toxic chemicals that are applied worldwide as household pesticides and for crop protection, and they are stockpiled for chemical warfare. As a result, they are routinely detected in air and water. Methods and routes of biodegradation of these compounds are being sought. We report that under aerobic, photosynthetic conditions, the cyanobacterium Anabaena sp. transformed methyl parathion first to o,o-dimethyl o-p-nitrosophenyl thiophosphate and then to o,o-dimethyl o-p-aminophenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…The reductive transformation of organophosphates that have nitro group, such as parathion (39), (41), and EPN (70), takes place in snails, crabs, Daphnia, and algae (Francis et al 1980;Megharaj et al 1994;Mostafa et al 1991;Takimoto et al 1987a). Barton et al (2004) confirmed that the nitroso derivative of (39) served as a reductive intermediate when metabolized by the blue-green alga Anabaena sp. Reductive debromination of leptophos (71) was reported by Francis et al (1980) in a model ecosystem study.…”
Section: Organophosphorus Pesticidessupporting
confidence: 75%
See 1 more Smart Citation
“…The reductive transformation of organophosphates that have nitro group, such as parathion (39), (41), and EPN (70), takes place in snails, crabs, Daphnia, and algae (Francis et al 1980;Megharaj et al 1994;Mostafa et al 1991;Takimoto et al 1987a). Barton et al (2004) confirmed that the nitroso derivative of (39) served as a reductive intermediate when metabolized by the blue-green alga Anabaena sp. Reductive debromination of leptophos (71) was reported by Francis et al (1980) in a model ecosystem study.…”
Section: Organophosphorus Pesticidessupporting
confidence: 75%
“…A similar approach was undertaken by using Anabaena sp. to examine the reduction mechanism of methyl parathion (39) (Barton et al 2004). A gene mutation relating to nitrate reduction did not affect the degradation of (39), and the transient formation of the nitroso derivative in the presence of light probability proceeded by the action of ferredoxin-NADP + reductase.…”
Section: Reductasesmentioning
confidence: 99%
“…Although in most of the studies on microbial degradation of parathion and methyl parathion, the first reaction was hydrolysis of the phosphotriester bond, there have been reports of different degradation pathways (Barton et al 2004;Munnecke and Hsieh 1976). In this work, we report that Bacillus sp.…”
Section: Introductionmentioning
confidence: 98%
“…Algae are known to be metabolically competent and active in the degradation of CPPs and other organic xenobiotics [4][5][6]. They are also ubiquitous in their distribution and are a vital part of nutrient cycles, involved in the fixation of both carbon and nitrogen.…”
Section: Introductionmentioning
confidence: 99%